ANALISIS AKUNTABILITAS BELANJA HIBAH PADA PEMERINTAH PROVINSI SUMATERA UTARA - Barus, Khairani Br; Nasution, Juliana (Bilancia : Jurnal Ilmiah Akuntansi, 2022)
ABSTRACT This study aims to analyze the accountability of grant spending to the Provincial Government of North Sumatra. This research is a qualitative research with an exploratory approach. The data used in this study were obtained by interviewing and documentation studies. It was concluded that from the six grant expenditure management processes, there is a process that every year experiences an obstacle, namely the reporting and accountability processes. These obstacles are (1) compliance, (2) the implementation of grant spending which takes a long time because it has to go through several stages, (3) the competence of human resources in the accountability and reporting process. Then communication and information must run well between the grant management and the grant recipients to achieve better accountability for grant spending. Socialization related to grant spending regulations also needs to be improved. Various efforts have been made to create accountability for grant spending in North Sumatra Province, among others, by providing the required report formats to make it easier for grantees and simplify the audit process. Keywords: Accountability, Grant Spending, Provincial Government ABSTRAK Penelitian ini bertujuan untuk menganalisa akuntabilitas belanja hibah pada Pemerintah Provinsi Sumatera Utara. Penelitian ini merupakan penelitian kualitatif dengan pendekatan eksploratif. Data yang digunakan dalam penelitian ini diperoleh dengan teknik wawancara dan studi dokumentasi disimpulkan dari keenam proses pengelolaan belanja hibah, terdapat proses yang setiap tahun mengalami sebuah kendala yaitu proses pelaporan dan pertanggungjawaban. Kendala-kendala tersebut adalah (1) kepatuhan, (2) pelaksanaan belanja hibah yang memerlukan waktu yang lama karena harus melewati beberapa tahapan, (3) kompetensi sumber daya manusia dalam proses pertanggungjawaban dan pelaporan. Kemudian komunikasi dan informasi harus berjalan dengan baik antara pihak pengelola hibah dengan pihak penerima hibah untuk mewujudkan akuntabilitas belanja hibah yang lebih baik. Sosialisasi terkait peraturan-peraturan belanja hibah juga perlu untuk ditingkatkan. Berbagai upaya telah dilakukan untuk menciptakan akuntabilitas belanja hibah pada Provinsi Sumatera Utara antara lain yaitu menyediakan format-format laporan yang dibutuhkan untuk mempermudah para penerima hibah dan mempermudah proses pemeriksaan. Kata Kunci: Akuntabilitas, Belanja Hibah, Pemerintah Provinsi